2005
DOI: 10.1099/mic.0.28184-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of Dam methylation in phase variation of Haemophilus influenzae genes involved in defence against phage infection

Abstract: Haemophilus influenzae uses phase variation (PV) to modulate the activity of its defence systems against phage infection. The PV of the restriction-modification (R-M) system HindI, the main defence system against phage infection and incoming chromosomal and phage DNA in H. influenzae Rd, is driven by changes of the pentanucleotide repeat tract within the coding sequence of the hsdM gene and is influenced by lack of Dam methylation. Phase-variable resistance/sensitivity to phage infection correlates with change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 34 publications
1
75
0
Order By: Relevance
“…Phase variation is a mechanism that has been shown to provide transient resistance to phage infection for Gram-negative bacteria (14,65). We identified seven unique putative phase variant mutations in this study, two of which were each found in two separate mutant strains.…”
Section: Discussionmentioning
confidence: 93%
“…Phase variation is a mechanism that has been shown to provide transient resistance to phage infection for Gram-negative bacteria (14,65). We identified seven unique putative phase variant mutations in this study, two of which were each found in two separate mutant strains.…”
Section: Discussionmentioning
confidence: 93%
“…Bacteria can switch on or off the expression of phage receptors 105,106 or secrete polysaccharides that limit the access to the receptor 107 . Bacterial hosts can also express membrane proteins that prevent injection of the viral genetic material into the cell 108 .…”
Section: Mechanisms Of Antiviral Defence In Prokaryotesmentioning
confidence: 99%
“…The effectiveness of RM systems in host protection against phage infection has been demonstrated in various studies reporting 10-to 10 8 -fold protection against phage infection (reviewed in reference 34). Interestingly, the expression of many RM systems is phase variable (35)(36)(37)(38), which has important evolutionary implications, which are discussed below.…”
Section: Restriction-modificationmentioning
confidence: 99%